Antecedent Employee Performance Implikasinya Pada Kinerja Karyawan PT. SAI Apparel Industries Semarang - Qoma'iroh, Syili; Ervina, Hawik; Setyorini, Noni (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2023)
The purpose of this research is to collect empirical evidence regarding the influence of job training, soft skills and hard skills on the performance of PT employees. Sai Apparel Industries Semarang. In this research, the population was 5,000 employees, sampling used probability sampling with simple random sampling techniques to obtain 130 samples. The data analysis technique used in this research is quantitative descriptive multiple linear regression analysis technique with IBM SPSS to process research data obtained through questionnaires, using the IBM SPSS 25 software tool. The results of hypothesis testing explain that (1) job training has an effect on employee performance, (2) soft skills have an effect on employee performance, (3) hard skills have no effect on employee performance.